P087 Providers' views on barriers and facilitators of bacterial STI testing among gbMSM living with or at risk for HIV. (14th July 2019) - Guiang, Charlie; Burchell, Ann; Rana, Jayoti; Shahin, Rita; Brunetta, Jason; Mitterni, Leo; Tan, Darrell; Bacon, Jean; Gilbert, Mark; Gesink, Dionne; Grewal, Ramandip; Logie, Carmen; et al.
Abstract : Background: Bacterial STI testing is a necessary component of sexual health care for MSM living with and at risk for HIV. Guidelines recommend testing at least once a year or more often if at ongoing risk. As part of a larger mixed methods study with the overall goal to prioritize new STI testing interventions, our aim was to determine barriers and facilitators to offering bacterial STI testing to MSM according to healthcare providers in Toronto, Canada. Methods: In 06/2018–07/2018, we circulated invitations for an online, anonymous survey to an estimated 172 providers in Toronto. Providers were eligible if they provided care for ≥1 MSM per week and were involved in the decision-making process in providing a STI test (e.g., taking sexual histories, ordering tests). Results: Of 93 respondents, 68% worked in primary care, 32% worked in public health/sexual health clinics, 70% were physicians and 30% were nurses or other allied health professionals. Most (67%) saw between 1–10 MSM clients per week. Among respondents working in primary care (n=63), barriers to offering testing 'sometimes' or more often were: insufficient consultation time (64%), difficulty introducing testing during unrelated consultations (52%), forgetting to offer testing (46%), patient reporting no sexual activity (30%) and patient refusal (25%). Among all respondents, preferred practice changes to improve testing were: express testing/fast-track testing services (89%), provider alerts when patients are due for testing (87%), selfcollected specimen sampling by patients (84%), standing orders for tests (79%), and nurse-led STI testing (78%). Primary care providers were more in favour of provider alerts whereas providers at sexual health clinics favoured patient reminders. Conclusion: Among those whose practice incorporated sexual health care for MSM, providers were in favour of initiatives to simplify and expedite bacterial STI testing (including self-collection of samples), prompts/reminders for testing, and expanding testing delivery to other healthcare professionals. Disclosure: No significant relationships.